The Influence of Cost Management Practices on Financial Performance of State-Owned Sugar Processing Companies in Nyanza, Kenya - Makori, Evans Onywere; Miroga, Julius (International Journal of Finance, 2025)
Purpose: This study explores the influence of cost management techniques on financial performance of state-owned sugar processing companies in Nyanza, Kenya. The study investigated the specific objectives; capital structure optimization, liquidity management, working capital optimization, and cost of capital management influence financial performance. Methodology: The study adopted a descriptive research design and purposive sampling technique to select the best sample for the study. The study population was 44 respondents. Data was collected using structured questionnaires and distributed using the drop-and-collect later method and later cleaned, sorted and coded in ordinal scale using numerical numbers and entered into Statistical Package for the Social Sciences (SPSS) software version 29 and the results presented in form of tables and figures. Quantitative data were analyzed through descriptive statistics, mean, correlation, and regression analysis. Findings: Correlation coefficient results for all the independent variables had a p-value of 0.000, which was less than 0.05 significant level, indicating a strong relationship with the dependent variable. The findings revealed that capital structure optimization and cost of capital management had strong, statistically significant positive effects on financial performance (p-values< 0.05). Liquidity management and working capital optimization were also positively correlated with financial outcomes, although their regression effects were less significant(p-values> 0.05). Unique Contribution to Theory, Policy and Practice: This study uniquely contributes to theory by expanding the Resource-Based View through empirical evidence linking cost management practices to financial performance in state-owned enterprises. It informs policy by highlighting the need for structured cost control frameworks in public sugar firms. Practically, it guides managers in adopting effective cost management strategies to enhance profitability, sustainability, and accountability in the sugar sector, fostering improved financial outcomes in Kenya’s public manufacturing enterprises. Recommendations include restructuring debt financing, implementing advanced liquidity forecasting models, and adopting innovative working capital tools to bolster profitability and financial stability.